Mengintegrasikan Kearifan Budaya Lokal Batik Garutan Melalui Pembelajaran SBDP di Sekolah Dasar - Hanifa, Syakira; Hidayah, Nurul (Indo-MathEdu Intellectuals Journal, 2024)
Local cultural wisdom has urgency for elementary school students as the nation's next generation so that they do not lose their identity and local culture can continue to be preserved. By integrating local culture such as Garutan batik in learning, it can increase feelings of love and also have an influence in shaping students' character. In practice, there are still obstacles such as a lack of teaching materials and a lack of materials needed to integrate Garutan batik by elementary school teachers in Garut Regency. Therefore, this research was created to discuss the integration of local Garutan batik culture in elementary schools. Using qualitative research methods, where data was obtained from the results of questionnaires with a total of 16 elementary school teachers in Garut Regency as respondents, which the researchers obtained using random sampling techniques. The results obtained were that in developing learning based on local wisdom really requires teacher creativity. One of the activities that can be carried out by students is batik making activities. Teachers can also develop teaching materials by carrying out various activities such as collaborating with local communities, cultural figures, or cultural experts